Irritant contact dermatitis determinants in fish cleaners: Occupational risk factors at paotere fish auction, Makassar - Ananda, Nur Aulia Ananda; Ibrahim, Irviani Anwar; Ekasari, Ranti; Habibi, Habibi (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2026)
Irritant contact dermatitis remains a common occupational skin disorder among workers exposed to repeated wet work and irritants, yet evidence on its determinants among fish cleaning workers in traditional fish auction settings remains limited; this study provides site-specific evidence from Paotere Fish Auction Site, Makassar. This study aimed to identify factors associated with symptoms of irritant contact dermatitis among fish cleaning workers. A quantitative cross-sectional study was conducted among all 118 fish cleaners using total sampling. Data were collected through structured questionnaires, observation sheets, and interviews. Univariate analysis was used to describe respondent characteristics, while bivariate associations were examined using the chi-square test and independent determinants were assessed using multiple logistic regression. Irritant contact dermatitis symptoms were reported by 66.1% of respondents. Age, working period, daily working duration, knowledge, use of personal protective equipment, and personal hygiene were significantly associated with symptoms in bivariate analysis (p<0.05). Multivariate analysis identified age, working period, knowledge, PPE use, and personal hygiene as significant determinants, with knowledge emerging as the most prominent modifiable factor. These findings emphasize the need for occupational health interventions focused on worker education, appropriate PPE use, improved personal hygiene, and safer workplace conditions to reduce occupational skin disease among fish cleaning workers.